Congklak as a Source of Ready to Wear Fashion Ideas: A Product Feasibility Study - Amalina Khairunnisa; Wulansari Prasetyaningtyas (Universitas Negeri Semarang, 2026)
Congklak is a traditional Indonesian game with cultural value, but is now being abandoned by Generation Z due to technological developments. One relevant cultural preservation effort is through fashion media, specifically readyto-wear clothing. This study aims to determine the level of feasibility of ready-to-wear clothing inspired by the game of congklak. The data collection method used an observation sheet. The assessment was carried out by 5 expert panelists and 15 trained panelists using an instrument covering six indicators, namely design, size, sewing technique, aesthetics, clothing performance, and special features. Data were analyzed using descriptive percentages. The results showed that the clothing obtained an average feasibility score of 90.89% and was included in the very feasible category. Thus, ready-to-wear clothing with a congklak theme was declared technically, functionally, and aesthetically feasible, and has the potential to become an alternative medium for cultural preservation. This study shows that the development of ready-to-wear clothing based on traditional games not only meets product feasibility standards but also has the potential to become an effective medium for reintroducing local culture to Generation Z.